EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN SMES: THE MEDIATING ROLE OF PSYCHOLOGICAL SAFETY - Fatwa Zuhaena; Heru Cahyo; Arinastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Small and medium enterprises (SMEs) increasingly require employees who are willing to contribute beyond formal job responsibilities to maintain organizational sustainability and competitiveness. Organizational citizenship behavior (OCB) consequently becomes an important organizational asset because voluntary employee behavior strengthens teamwork, flexibility, and organizational effectiveness. This study aims to examine the relationships among employee engagement, psychological safety, and organizational citizenship behavior, as well as the mediating role of psychological safety among SME employees in Indonesia. This study employed a quantitative approach using a cross-sectional survey design. Data were collected from 198 SME employees through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that employee engagement positively affects psychological safety and organizational citizenship behavior. Psychological safety also positively influences organizational citizenship behavior and significantly mediates the relationship between employee engagement and organizational citizenship behavior. The study confirms that engaged employees are more likely to demonstrate extra-role behavior when they perceive psychologically safe workplace environments characterized by trust, openness, and supportive interpersonal relationships. The findings strengthen Social Exchange Theory in explaining reciprocal employee behavior within SME environments and provide practical implications for developing supportive organizational climates that encourage voluntary employee participation and organizational sustainability. Keywords: Employee Engagement; Psychological Safety; Organizational Citizenship Behavior; SMEs; Social Exchange Theory